Pengadaan Tanah dan Asas Keselarasan: Menelaah Pasal 49A PP Nomor 39 Tahun 2023: Land Acquisition and the Harmony Principle: Examining Article 49A of Regulation 39/2023 - Nugraha, Muhammad Kemal Syah; Koeswahyono, Imam; Adianto, Daru (WARKAT, 2026)
Land acquisition for public interest is a vital instrument in accelerating national development, which must be grounded in the principles of justice and harmony. However, the enactment of Government Regulation Number 39 of 2023 introduces significant deregulation through Article 49A paragraph (1) letter a, which eliminates the requirement for Confirmation of Spatial Utilization Activities (KKPR) after the determination of the project location. This research aims to analyze the legal problems arising from the elimination of the KKPR requirement from the perspective of the principle of harmony, and to seek solutions for the norm conflicts between accelerated development policies and the principles of sustainable spatial planning. The research method employed is normative legal research with a statutory approach, a conceptual approach, and a case approach. The results indicate that the removal of the KKPR requirement creates legal disharmony that paralyzes the control function of spatial utilization and potentially triggers agrarian conflicts, as observed in the Rempang Eco City case. This deregulation is considered to violate the principle of harmony as it prioritizes investment and state interests unilaterally over the protection of community rights and spatial order. Therefore, regulatory synchronization is required to restore the function of KKPR as a primary verification instrument to ensure balanced and equitable development.